Defining Bisexuality: Young Bisexual and Pansexual People's Voices. Issue 1 (2nd January 2017) - Flanders, Corey E.; LeBreton, Marianne E.; Robinson, Margaret; Bian, Jing; Caravaca-Morera, Jaime Alonso
ABSTRACT: Bisexuality is defined in a plethora of ways, including definitions based on behavior, attraction, or desire and may employ binary or nonbinary definitions. Research has not adequately addressed how young bisexual people themselves define bisexuality, whether those definitions change with social context, or whether bisexual people define bisexuality differently from pansexual people. The current study addresses these questions through an online, mixed-methods study. A total of 60 bisexual and pansexual participants aged ages 18 to 30 responded to closed- and open-ended questions regarding their definitions of bisexuality. Closed-ended responses were analyzed with a series of chi-square tests, while we conducted a summative content analysis on the open-ended responses. Results indicate that in general, bisexual and pansexual people define bisexuality similarly. Participants modified their definitions of bisexuality depending upon the social context. Implications for research are discussed.